Monitoring of environmental variations of marshes in Iraq using Adaptive classification method. - Abed- Al-Razaq, Ban; Kamil Shnain, Saif; Abd Al-Hamza, Sara Jawad (Iraqi Journal of Science, 2023)
The object of the presented study was to monitor the changes that had happenedin the main features (water, vegetation, and soil) of Al-Hammar Marsh region. Tofulfill this goal, different satellite images had been used in different times, MSS1973, TM 1990, ETM+ 2000 and MODIS 2010. K-Means which is unsupervisedclassification and Neural Net which is supervised classification was used to classifythe satellite images 0Tand finally by use 0Tadaptive classification 0Twhich is0T3T 0T3Tapplys0Tupervised classification on the unsupervised classification. ENVI soft where usedin this study.